Aplicyanins - Brominated natural marine products with superbasic character - Alzoubi, Basam; Puchta, Ralph; et al. (Zeitschrift für Naturforschung - Section B Journal of Chemical Sciences, 2016)
By using quantum chemical methods (B3LYP/6-311+G(2df,p)//B3LYP/6-31G(d)), we investigated the structures of aplicyanin A, aplicyanin B, aplicyanin C, aplicyanin D, aplicyanin E, and aplicyanin F along with their protonated structures. The calculated gas phase proton affinities of aplicyanin A, aplicyanin C, and aplicyanin E are around -250 kcal mol-1 and therefore more than 10 kcal mol-1 higher as in typical proton sponges such as 1,8-bis(dimethylamino)naphthalene. The compounds aplicyanin B, aplicyanin D, and aplicyanin F show reduced proton affinities of approximately -240 kcal mol-1 because of the acetyl group being conjugated with the imine N=C moiety. Nucleus-independent chemical shift (NICS) calculations on the same level of theory do not show any peculiarities, and a reasonable correlation between the toxicity of aplicyanins and the gas phase proton affinity is not observed.
CRIS-Team Scopus Importer:2026-01-22
Keywords: Aplicyanin; DFT; Gas phase proton affinity; Proton sponges